Training and Capacity Building: what value and what next for ADR UK? - Oliver, Emily (International Journal of Population Data Science, 2025)
Objective Approaching the end of ADR UK’s current investment period, we reflect on the value added through training and capacity building (TCB) and how we should shape our future plans to support increased use of administrative data. Method ADR UK’s Training and Capacity Building Strategy (2021) aimed to identify and create pathways to scale up the use of administrative data. It spanned audiences by level and discipline, endeavouring to raise awareness as well as build the confidence of potential users by offering skills development opportunities and providing access to experts. To prepare for our next phase we have evaluated these activities to calculate their worth. In parallel, we have surveyed our users to identify gaps that need filling. These two approaches provide the basis for the next TCB strategy. Results We will present the results of the economic evaluation of our TCB activities including investment in PhD studentships; provision of courses and dataset-specific resources; and describing the extent of our reach geographically across the partnership. We will share findings from a recent survey of researchers’ needs identifying gaps in provision. We will explain how we intend to collaborate across the ADR UK partnership and other ESRC investments to support data-driven research skills for administrative data research and across multiple types of data through a range of creative mechanisms for learning. Conclusion The economic evaluation of our TCB work to date provides a steer for the future. But we need to marry that with researcher needs and evolving research potential as new forms of data are made available and new mechanisms for access emerge. As ADR UK’s remit expands, we will be looking to pivot our TCB activity to meet demand by collaborating more closely across the partnership to increase efficiency, including through further progress on the provision of synthetic data. We will draw on stakeholders across the data community for ideas and examples for building capacity and streamlining processes.